Audiological characteristics and cochlear implant outcome in children with cochlear nerve deficiency - Ren, Cuncun; Lin, Ying; Xu, Zhuo; Fan, Xiaoqin; Zhang, Xinyu; Zha, Dingjun (Frontiers in Neurology, 2022)
Objectives This study aimed to examine the audiological characteristics and validity of predicting outcomes of cochlear implants (CIs) in children with cochlear nerve deficiency (CND) based on the internal auditory meatus (IAM) nerve grading system. Methods The audiological characteristics of 188 ears in 105 children diagnosed with CND were analyzed based on the IAM nerve grading system. In addition, 42 children with CND who underwent CI were also divided into four groups based on the system, and their auditory and speech performance at baseline (preoperative) and 6, 12, and 24 months after CI were analyzed and compared with those of the control group (n = 24) with a normal cochlear nerve (CN) and CI. Results The audiological test results showed no significant differences among the four CND groups in terms of elicited rates of distortion product otoacoustic emission (DPOAE) (p = 1.000), auditory brainstem response (ABR) (p = 0.611), and cochlear microphonic (CM) (p = 0.167). Hearing in the CND IV group was significantly better than that in the CND I group (p < 0.05). In children with CI, the auditory and speech performance of the control group was significantly higher than all CND groups from 6 to 24 months (p < 0.05) and 12 to 24 months (p < 0.05), respectively. Meanwhile, there were no significant differences between each pair group in the four CND groups (p > 0.05). Conclusion Children with CND, including those in whom the CN was not visualized by MRI, can benefit from CI. Additionally, the IAM nerve grading system could not predict the outcomes of CI in children with CND.